Ancient Adaptive Evolution of Tetherin Shaped the Functions of Vpu and Nef in Human Immunodeficiency Virus and Primate Lentiviruses - Lim, Efrem S. (American Society for Microbiology (ASM), 2010)
Tetherin/BST-2 is a host-encoded protein that restricts a wide diversity of viruses at the stage of virion release. However, viruses have evolved antagonists of Tetherin, including the Vpu and Nef proteins of primate lentiviruses. Like other host genes subject to viral antagonism, primate Tetherin genes have evolved under positive selection. We show here that viral antagonists acting at three independent sites of selection have driven the evolution of Tetherin, with the strongest selective pressure on the cytoplasmic tail domain. Human Tetherin is unique among the Tetherins of simian primates in that it has a 5-amino-acid deletion that results in the loss of the residue under the strongest positive selection. We show that this residue at amino acid 17 is the site of the functional interaction of Tetherin with Nef, since single amino acid substitutions at this single position can determine the susceptibility of Tetherin to Nef antagonism. While the simian immunodeficiency viruses SIVcpz and SIVgor are able to antagonize their hosts' Tetherin with Nef, human immunodeficiency virus type 1 (HIV-1) Vpu has evolved to counteract Tetherin in humans. We mapped the adaptations in the N-terminal transmembrane domain of Vpu that allow it to counteract human Tetherin. Our combined evolutionary and functional studies have allowed us to reconstruct the host-pathogen interactions that have shaped Tetherin and its lentivirus-encoded antagonists.